Ideological Framing, Mosques, and Conflict: Bargaining Position of Salafi Movement in Lombok, East Indonesia - Saparudin, Saparudin; Emawati, Emawati (Journal of Al-Tamaddun, 2023)
The Salafi movement is a transnational Islamic group that uses mosques to mobilize its followers and promote its ideological framing. The differences in understanding and practicing religious rituals and worship between the Salafi and mainstream Islamic organizations, such as Nahdlatul Ulama (NU) and Nahdlatul Wathan (NW), have triggered tensions and social conflicts during the construction of new Salafi mosques. Therefore, this study aimed to analyze how Salafi strengthened its existence amid the conflicts by disseminating its ideological framing through the new mosque on the Island of Lombok, Indonesia. Based on the theory of social movement as the cognitive framework, this study also argued that although the ideological framing propagated by Salafi through its mosques fueled social conflicts, it became the strategy for bargaining position amid the mainstream Muslims in Lombok. The emergence of the conflicts was used as the reason for the Salafi group to build new mosques or seize control of pre-existing mosques. This condition did not undermine Salafi as a minority and a new emerging Islamic group. Instead, it empowers the bargaining position of the transnational Islamic group in its own right. For Salafi, owning and controlling the holy places is the opportunity to mobilize collective actions and its social proponents to disseminate the Manhaj Salaf ideology. In conclusion, this study contributed to explicating the dynamics of local Salafi in the discourses of the contemporary global Islamic movement.